Education effects on the medication adherence level in type 2 dm patients - Imas Masliyah; Dayan Hisni; Nita Sukamti (Science Midwifery, 2023)
Education is the primary basis for the perfect treatment and prevention of Diabetes Mellitus. Minimum knowledge about Diabetes Mellitus will lead to complications more quickly, burdening the family and society. This research design is experimental research with a Quasi-Experimental Design in the form of a "Two Group Pretest-posttest." The sample in this study was 50 people using the entire population. This research was conducted at the Kedaung Kaliangke Public Health Center, West Jakarta. Preliminary data collection was started in November 2022-December 2022, and the research was conducted from January 2023. The data analysis technique used the paired t-test. This research can be concluded that there was an effect of education on the adherence level in taking medication in patients with type 2 DM at the Kedaung Kaliangke Health Center Jakarta in the instrument group and the control group.